2017
DOI: 10.1016/j.ctcp.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an add-on treatment with the homeopathic medication SilAtro-5-90 in recurrent tonsillitis: An international, pragmatic, randomized, controlled clinical trial

Abstract: ISRCTN registry: Registration number ISRCTN19016626, registered 23 January 2013.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 26 publications
0
13
0
3
Order By: Relevance
“…46 Adjunctive treatment is another choice wherein homoeopathy has a potential role to play in integrative patient care. 39,41,53 Homeopathic remedies are generally regarded as safe. 27,38,55,67 However, it is not absolutely devoid of risks and a few mild adverse events were reported in the reviewed studies.…”
Section: Discussion Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…46 Adjunctive treatment is another choice wherein homoeopathy has a potential role to play in integrative patient care. 39,41,53 Homeopathic remedies are generally regarded as safe. 27,38,55,67 However, it is not absolutely devoid of risks and a few mild adverse events were reported in the reviewed studies.…”
Section: Discussion Summarymentioning
confidence: 99%
“…A study 38 on 30 patients suffering from viral tonsillitis by Malapane et al found that homeopathic complex medicine exhibited significant anti-inflammatory and pain-relieving properties without any adverse events. An international, pragmatic, randomised, controlled clinical trial by Palm et al 39 on recurrent tonsillitis with a sample size of 256 patients investigated SilAtro-5-90 (Atropinum sulfuricum, Mercurius bijodatus, Hepar sulphur, Kali bichromicum and Silicea) 'in' addition to standard treatment. They suggested an integrative treatment may bring the therapeutic benefit to patients.…”
Section: Randomised Clinical Trialsmentioning
confidence: 99%
“…The primary outcome for the model is the incremental cost per ATI averted. Estimates of the recurrence of ATIs following intervention are drawn from an open-label multi-centre randomised controlled trial of SilAtro-5-90 [ 16 ] for individuals with moderate recurrent tonsillitis in 19 study centres across Germany, Spain and the Ukraine. Moderate recurrent tonsillitis was defined as experiencing at least 3 ATIs in the prior 12 months or 2 ATIs in each of the previous 2 years.…”
Section: Methodsmentioning
confidence: 99%
“…A multicentre randomised clinical trial of patients experiencing recurrent tonsillitis found that the risk of having an ATI was significantly lower in patients treated with conventional symptomatic medication together with SilAtro-5-90 (intervention group) than in those treated with conventional symptomatic medication alone (usual care group). At the same time, the adjuvant SilAtro-5-90 plus usual care group had a significantly reduced use of antibiotic medication, and a lower number of days absent from work or school when experiencing an ATI [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…В ходе исследований было продемонстрировано значительное снижение частоты рецидивов (более чем в 2 раза) и увеличение среднего времени ремиссии (практически в 3 раза) при применении Тонзилотрена в комплексной терапии. Кроме того, использование Тонзилотрена позволило сократить частоту применения антибиотиков в 1,6 ра за [18,19].…”
unclassified